1984
DOI: 10.1128/aem.47.5.1054-1061.1984
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria associated with crabs from cold waters with emphasis on the occurrence of potential human pathogens

Abstract: A diverse array of bacterial species, including several potential human pathogens, was isolated from edible crabs collected in cold waters. Crabs collected near Kodiak Island, Alaska, contained higher levels of bacteria than crabs collected away from regions of human habitation. The bacteria associated with the crabs collected near Kodiak included Yersinia enterocolitica, Klebsiella pneumoniae, and coagulasenegative Staphylococcus species; the pathogenicity of these isolates was demonstrated in mice. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 45 publications
0
17
0
1
Order By: Relevance
“…Haemoglobins derived from marine organisms may be another source of haem-iron for V. cholerae. Studies have shown that a variety of filter-feeding marine organisms accumulate V. cholerae to high levels when exposed to sea water containing V. cholerae (Faghri et al, 1984;Murphree and Tamplin, 1995). The persistence of V. cholerae within these hosts may be determined by the availability of nutrients such as iron.…”
Section: Discussionmentioning
confidence: 99%
“…Haemoglobins derived from marine organisms may be another source of haem-iron for V. cholerae. Studies have shown that a variety of filter-feeding marine organisms accumulate V. cholerae to high levels when exposed to sea water containing V. cholerae (Faghri et al, 1984;Murphree and Tamplin, 1995). The persistence of V. cholerae within these hosts may be determined by the availability of nutrients such as iron.…”
Section: Discussionmentioning
confidence: 99%
“…Aeromonas species have been reported in both untreated and chlorinated drinking water (LeChevallier et al 1980(LeChevallier et al ,1982Burke et al 1984b. The organism is commonly isolated from fish (Boulanger et al 1977) and shellfish (Konuma et al Faghri et al 1984). Incidences of human Aeromonas gastroenteritis have been attributed t o both contaminated water (Davis et al 1978;Kipperman et al 1984) and fish (Kalina 1977).…”
Section: Ecologymentioning
confidence: 99%
“…Commerce, 1990). Microbial studies conducted on Alaskan seafoods have included: salmon (Snow and Beard, 1939;Elliot, 1987a), pollock surimi (Elliot, 1986(Elliot, , 1987bHimelbloom et al, 1991a,b), native seafoods (Zottola et al, 1983), and shellfish (Faghri et al, 1984;Kaysner, 1981;Vasconcelos et al, 1975). Microbiological data are essential for evaluating seafood quality and for developing seafood processing guidelines.…”
Section: Introductionmentioning
confidence: 99%